Transcriptional profiling identifies critical steps of cell cycle reprogramming necessary for Plasmodiophora brassicae‐driven gall formation in Arabidopsis. (5th January 2019) - Olszak, Marcin; Truman, William; Stefanowicz, Karolina; Sliwinska, Elwira; Ito, Masaki; Walerowski, Piotr; Rolfe, Stephen; Malinowski, Robert
Summary: Plasmodiophora brassicae is a soil‐borne biotroph whose life cycle involves reprogramming host developmental processes leading to the formation of galls on its underground parts. Formation of such structures involves modification of the host cell cycle leading initially to hyperplasia, increasing the number of cells to be invaded, followed by overgrowth of cells colonised by the pathogen. Here we show that P. brassicae infection stimulates formation of the E2Fa/RBR1 complex and upregulation of MYB3R1, MYB3R4 and A‐ and B‐type cyclin expression. These factors were previously described as important regulators of the G2−M cell cycle checkpoint. As a consequence of this manipulation, a large population of host hypocotyl cells are delayed in cell cycle exit and maintained in the proliferative state. We also report that, during further maturation of galls, enlargement of host cells invaded by the pathogen involves endoreduplication leading to increased ploidy levels. This study characterises two aspects of the cell cycle reprogramming efforts of P. brassicae : systemic, related to the disturbance of host hypocotyl developmental programs by preventing cell cycle exit; and local, related to the stimulation of cell enlargement via increased endocycle activity. Significance Statement: We describe the changes in host cell cycle gene expression in response to P. brassicae infection, and characterise the impact of key cell cycle regulators (MYB3R4, E2Fa, CCS52A1), establishing that cell proliferation during gall development stems from repression of cell cycle exit, whereas hypertrophy in later disease stages depends on stimulation of endoreduplication. This provides a molecular framework for understanding the progress of clubroot disease and gall formation.